Shielding effect in pile groups adjacent to deep unbraced and braced excavations - Nishanthan, R.; Liyanapathirana, D.S.; Leo, C.J. (Taylor & Francis Group, LLC, 2016)
This paper investigates the shielding effect within piles in a group adjacent to deep unbraced and braced excavations. Numerical simulations based on the finite element method are performed on free-head and capped-head piles in three different pile group configurations. The numerical model is validated by simulating a series of centrifuge tests. The problem was modelled considering the three-dimensional geometry, which facilitates to simulate the shielding effect of piles within the group during an excavation. Results show that the presence of front piles near the excavation face reduces the detrimental effects on the rear piles within the group in unbraced excavations. In addition, the provision of a pile cap significantly reduces the deflection of pile group in unbraced excavations due to load transfer to rear piles, which are located away from the excavation. However, in braced excavations, unless the excavation is deep, the shielding effect and the presence of a pile cap are less significant on the pile group behaviour.
Keywords: Pile group; Unbraced/braced deep excavations; Shielding effect; Ground movements; Finite element method